Genotyping of Pneumocystis jirovecii by Use of a New Simplified Nomenclature System Based on the Internal Transcribed Spacer Regions and 5.8S rRNA Gene of the rRNA Operon - Xue, Ting (J Clin Microbiol, 2019)
Genotyping based on internal transcribed spacer 1 (ITS1) and ITS2 of the rRNA operon has played an important role in understanding the transmission and epidemiology of Pneumocystis jirovecii, one of the major opportunistic pathogens in individuals with AIDS and other immunocompromised individuals. The widespread use of this typing system has resulted in several problems, including inconsistent genotype nomenclatures, difficult data transferability, and complicated interpretation of the length variation in multiple homopolymeric tracts. The aim of this study was to establish a new, simplified genotype nomenclature system for P. jirovecii based on the ITS1 and ITS2 sequences. We first analyzed the complete ITS1, 5.8S rRNA gene, and ITS2 sequences (termed ITS1-5.8S-ITS2) in 27 recent P. jirovecii isolates from China and identified 18 unique genotypes. Subsequently, we performed a comprehensive classification of more than 400 ITS1- and ITS2-related sequences from GenBank and an in-depth evaluation of the length variation of multiple homopolymeric tracts within ITS1-5.8S-ITS2. Integration of the results from these analyses led to a new, simplified genotype nomenclature system including 62 unique ITS1-5.8S-ITS2 genotypes, simply designated types 1 through 62. This new system offers several advantages over traditional ITS1- and ITS2-based typing systems, including a simpler analysis and interpretation process, a higher discriminative power, and no limitation in assigning potential new genotypes. This new system is expected to facilitate the standardization of P. jirovecii genotyping and easy data exchanges across different laboratories.